The engineering support of technologies of the power complex; Korus 2005; Vol. 1 - Leonov S. V. Sergey Vladimirovich; Muravlev O. P. Oleg Pavlovich; Kalaev V. E.; Fedyanin A. L. Alexander Leonidovich (2005, 2005)
Program is based on the mathematical model, which represents a special case of solving of basic Macsvell's simultaneous equations and describes electromagnetic processes per the solving of stationary magnetic fields. The program of solving the magnetic fields is developed in an integrated environment, which is called MatLab and has friendly user interface with an ability of graphical performance of three-dimensional geometry and volumetric allocation of the magnetic field characteristics in the investigation area.